2020
DOI: 10.1111/papr.12953
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Erector Spinae Plane Block for Postoperative Analgesia in Laparoscopic Cholecystectomy: A Systematic Review and Meta‐analysis of Randomized Controlled Trials

Abstract: Background: Erector spinae plane (ESP) block is a novel regional anesthetic technique. Its application for postoperative analgesia has been increasing since 2016; however, its effectiveness remains uncertain and varies according to the type of surgery. This meta-analysis aimed to assess the analgesic efficacy of ESP block in patients undergoing laparoscopic cholecystectomy. Methods: Literature searches of electronic databases and manual searches up to June 1, 2020 were performed. Review Manager Version 5.3 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Serratus intercostal plane block provides sensory block of T7-T11 dermatomes but is insufficient for midline incisions [6,7,13]. Nevertheless, procedures such as quadratus lumborum blocks, erector spina plane blocks, and thoracic epidural catheters, which give adequate analgesia in laparoscopic cholecystectomy operations, are among the regional anesthesia treatments that cannot be applied or are difficult to apply in the supine position [14][15][16][17][18]. TAPA and m-TAPA blocks were used in the present study after anesthesia induction in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Serratus intercostal plane block provides sensory block of T7-T11 dermatomes but is insufficient for midline incisions [6,7,13]. Nevertheless, procedures such as quadratus lumborum blocks, erector spina plane blocks, and thoracic epidural catheters, which give adequate analgesia in laparoscopic cholecystectomy operations, are among the regional anesthesia treatments that cannot be applied or are difficult to apply in the supine position [14][15][16][17][18]. TAPA and m-TAPA blocks were used in the present study after anesthesia induction in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…The TAP block is a feasible and effective technique for multimodal analgesia following LSG, 21 , 22 while the ESP block 23 , 24 is an effective but relatively new technique to block the spinal nerves innervating the anterior abdominal wall to control postoperative pain after laparoscopic surgery. 25 , 26 Currently, there is insufficient literature comparing ultrasound-guided TAP or ESP blocks with the PLPLAT in terms of efficacy and time required to perform the blocks. 27 , 28 Further studies are needed to assess the efficacy and duration of procedure between PLPLAT and TAP block.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, In a recent article in this journal, Daghmouri et al 1 reported the findings of a systematic review and metaanalysis of randomized controlled trials (RCTs) of the use of bilateral erector spinae plane block (ESPB) for postoperative analgesia following laparoscopic cholecystectomy. The use of ESPB for a wide range of indications has increased exponentially 2 and there is a clear need for definitive answers about the efficacy of ESPB.…”
mentioning
confidence: 99%
“…The use of ESPB for a wide range of indications has increased exponentially 2 and there is a clear need for definitive answers about the efficacy of ESPB. Daghmouri et al 1 found that bilateral ESPB appears to improve the quality of analgesia in the first 24 postoperative hours, and concluded that ESPB is a safe effective alternative option for pain management following laparoscopic cholecystectomy. However, the efficacy of ESPB, and indeed the very concept of interfascial plane blocks, has recently been subjected to scrutiny.…”
mentioning
confidence: 99%
See 1 more Smart Citation